The development of the method of multifactor authentication based on hybrid cryptocode constructions on defective codes - Yevseiev, Serhii; Kots, Hryhorii; Minukhin, Sergii; Korol, Olga; Kholodkova, Anna (Eastern-European Journal of Enterprise Technologies, 2017)
The proposed security mechanisms in hybrid-crypto-code systems, based on Niederreiter and McEliece modified asymmetric crypto-code systems on flawed codes allow further use of the methods of strict two-factor authentication on OTP passwords (OTP based 2FA). To ensure the required security and efficiency in the multi-factor authentication protocol, the McEliece and Niederreiter modified asymmetric crypto-code systems, allowing integrated reliability provision in information transmission on the basis of error-correction coding on elliptic codes are used. The use of the MV2 algorithm ensures an increase in the total entropy of the key and the physical separation of the transmission of the authenticator parts by various mobile/Internet communication channels based on multi-channel cryptography systems on flawed codes. The proposed mathematical models and algorithms for the practical implementation of the Niederreiter and McEliece HCCSFC make it possible to significantly reduce the energy capacity of group operations by reducing the power of the Galois field to GF 24–26 by additional transformations based on the MV2 algorithm, ensuring the required cryptographic strength